An Overview: The Effects of Particulate Matters, an Important Atmospheric Pollutant, on the Spread of Covid19 - Zeynep Ceylan; Åžahin Korkmaz (Universitas Airlangga, 2021)
Introduction: This review deals with research and scientific perspectives about whether there is any effect linked to particle size and structure of one of the significant atmospheric pollutants of particulate matter (pm) on the duration of residence in air and transport of the virus causing Covid19, originating in China and becoming a global pandemic in 2020, and hence whether pm may change the level of effectiveness of the virus in humans. Discussion: The virus causing Covid19 may bind (adsorption) to the surface of particles classified as fine particles and use these particles as transporters. These may easily pass into the throat and lungs of people via inhalation and cause deadly disease, as revealed by the results of scientific research. Fine particles may display variability in terms of chemical properties, emission density, degradation duration, and long- and short-distance transport properties, in addition to precipitation or suspension mechanisms. Conclusion: In this study, a review was prepared by investigating research performed since 2020 about the correlations between the virus causing Covid19, continuing to have deadly effects worldwide, with pm density and particle diameter to provide a guide for future studies.